Effect of social media engagement, corporate image and perceived value on tourist loyalty in hotel industry in Malaysia - Khan, Md. Ashraful Azam (2022)
Nurturing tourist loyalty is a top priority for Malaysian hotels in the contemporary competitive business environment. In recent years, tourist loyalty in the Malaysian hotel industry has declined which negatively impacted hotels’ occupancy rates and survival. For instance, according to a hotel survey report released by Tourism Malaysia (2020), the hotel occupancy rate in the industry recorded a 2% decline in 2019 compared to 2018. Furthermore, the recent surge in the Covid-19 pandemic exacerbated the situation and hit the hotel industry hard, resulting in many hotels being temporarily or permanently closed. Scholars and industry experts have postulated that effective customer social media engagement and the repositioning of hotels with a positive corporate image are effective for the resurgence in the post-pandemic era. Despite the growing interest in social media engagement and corporate image to enhance the perceived value of tourists to generate loyalty in the hospitality industry, the empirical evidence for linking these constructs is still limited. In particular, from the perspective of the hotel industry, little effort has been made to explore the mediating role of perceived value in the relationship between social media engagement and tourist loyalty, and between corporate image and tourist loyalty. Therefore, the general purpose of this study is to investigate the impact of social media engagement, corporate image, and perceived value on tourists’ loyalty to the Malaysian hotel industry. Using the quantitative methodology, a self-administrative questionnaire was used to collect data from Malaysian and international hotel customers via online (email, WhatsApp, Facebook) and face-to-face data collection methods. A total of 360 samples were used for data analysis. Structural equation modeling (SEM) results using Smart-PLS suggests that social media engagement does not have a direct positive impact on tourist loyalty. However, social media engagement positively influences tourist loyalty through the mediating effect of perceived value in the hotel industry. While perceived value and corporate image show a direct positive impact on tourist loyalty. Corporate image through the mediating effect of perceived value was found to have a substantial effect on tourist loyalty. Theoretically, the outcome of this study supports the generally discussed theories to examine the relationship between ii social media engagement, corporate image, perceived value, and tourist loyalty to better understand the complex relationships (antecedents and consequences) among these constructs in the hotel sector. Practically, findings from this study would benefit the hoteliers in Malaysia to have better insights into recognizing social media engagement and corporate image as a powerful marketing tool to influence their customers’ perceived value and loyalty towards the hotels. Limitations of the study were also highlighted. One of the major limitations of this study is that due to Covid-19 pandemic lockdowns, it was not possible to collect data proportionately from the Malaysian and international tourist groups. Therefore, only 81 (23%) of the 360 respondents were international tourists, thus the sample may not be a complete representation of the population under study. Finally, recommendations for future research were discussed.